KEJADIAN PENYAKIT MOSAIK DANVARIETAS TAHANCUCUMBER MOSAIC VIRUS (CMV) PENYEBAB PENYAKIT MOSAIK PADA TANAMAN MENTIMUN - Pandawani, Ni Putu; Hanum, Farida; Ariati, Eka Pasmidi (Agrimeta: Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2018)
Virus-borne disease is a major constraint in increasing cucumber production in most cucumber planting sites in Indonesia including cucumber planting in Baturiti, Tabanan Bali. Based on the research of Balitsa (2006), it is generally said that the losses due to virus attack can range from 10% to 90%, depending on various aspects related to how the cultivation pattern is done. The existence of difficulties in the control of this virus encourages the effort to get a cucumber plant that resists viruses as problem solving. This study aimed to determine the cause of mosaic disease incidence in cucumber cultivation in Baturiti, Tabanan Bali and looked for cucumber varieties that are resistant to infection of viral pathogen causing the mosaic disease. The survey of disease incidence and symptom disease observation were done in several cucumber planting centers covering the whole plant population and the number of symptomatic plants in each observation location. For identification of the virus causing mosaic disease in the cucumber plant, the cucumber leaf sample showing symptoms was collected from several cucumber plant sites. Then the sample was tested by Elisa using the antiserum CMV, WMV and PRsV. For resistance tests, the cucumber varieties that were commonly grown by local farmers are mechanically transmitted from the CMV inoculum source sap. From the results of this study, it can be concluded that the incidence of mosaic disease in cucumber cultivation in Baturiti, Tabanan Bali ranged between 83.59% and 85.21% and dominantly induced by CMV. There were no common varieties in locally grown farmers resistant to CMV, but the moderately sensitive Harmony varieties deserved attention to keep being cultivated.